Trend of knowledge production of research centers in the field of medical sciences in iran. - K Falahat; Mb Eftekhari; E Habibi; Sh Djalalinia; N Peykari; P Owlia; H Malekafzali; M Ghanei; Sh Mojarrab (Tehran University of Medical Sciences, 2013)
Establishment of medical research centers at universities and health-related organizations and annually evaluation of their research activities was one of the strategic policies which followed by governmental organization in last decade in order to strengthening the connections between health research system and health system. The aim of this study is to scrutinize the role of medical research centers in medical science production in Iran. This study is a cross sectional which has been performed based on existing reports on national scientometrics and evaluation results of research performance of medical research centers between years 2001 to 2010. During last decade number of medical research centers increased from 53 in 2001 to 359 in 2010. Simultaneous scientific output of medical research centers has been increased especially articles indexed in ISI (web of science). Proper policy implementation in the field of health research system during last decades led to improving capacity building and growth knowledge production of medical science in recent years in Iran. The process embedding research into the health systems requires planning up until research products improves health outcomes and health equity in country.